2002
DOI: 10.1034/j.1398-9995.2002.13118.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational contact urticaria from diglycidyl ether of bisphenol A epoxy resin

Abstract: Our case is of interest, first, because contact urticaria from ER is very rare, and second, because this is the second report in which a strongly intensified contact urticaria reaction was provoked by an alcohol solution. We suggest that if the contact urticaria provocation test with low-molecular-weight chemicals is negative, a contact urticaria provocation test with alcohol (CUPTA) should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The reason we used a number of different cell lines to study the effect of HEMA and NAC is that HEMA may usually come in contact with a variety of cell types including the immune cells, oral keratinocytes, and osteoblasts because HEMA is usually used in dental restorative materials and endodontic sealers and is a known inducer of contact dermatitis in skin (8,29) as well as hypersensitivity in the oral cavity. Furthermore, we wanted to see whether there was differential sensitivity to HEMAinduced cell death in different cell types.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason we used a number of different cell lines to study the effect of HEMA and NAC is that HEMA may usually come in contact with a variety of cell types including the immune cells, oral keratinocytes, and osteoblasts because HEMA is usually used in dental restorative materials and endodontic sealers and is a known inducer of contact dermatitis in skin (8,29) as well as hypersensitivity in the oral cavity. Furthermore, we wanted to see whether there was differential sensitivity to HEMAinduced cell death in different cell types.…”
Section: Resultsmentioning
confidence: 99%
“…Although the use of these resin-containing materials is beneficial to patients, they carry the risk of local and systemic adverse effects. The potential risks are direct damage to the cells (cytotoxicity) and immunemediated responses (allergy) (7,8). We have previously shown that HEMA and triethyleneglycol dimethacrylate (TEGDMA) are released in vitro from many resin-based tooth restorative materials used in dentistry in microgram to milligram amounts in the first days after placement of clinically used amounts of the source materials (9 -12), and they are cytotoxic to the pulp (13).…”
mentioning
confidence: 99%
“…A few cases of immediate allergy to ERs – mostly cases of contact urticaria – have been reported [10,11,12,13,14]. Only one previous report describing OA with coexistence of immediate allergy to ER could be identified [2].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, organic acid anhydride hardeners and epoxy resins (Jolanki et al 1997a,b;Iolanki et al 2000;Kanerva et al 2002b) should be regarded as potential causes of the contact-urticaria syndrome . In particular, organic acid anhydride hardeners and epoxy resins (Jolanki et al 1997a,b;Iolanki et al 2000;Kanerva et al 2002b) should be regarded as potential causes of the contact-urticaria syndrome .…”
Section: Contact Urticariamentioning
confidence: 99%